Tax Control System of Transfer Pricing with the Beps Plan - M. Tufetulov, Aidar; Sh. Nugayev, Fatih; S. Zayats, Andrey (International Journal of Engineering and Technology, 2018)
The paper considers the basic principles of the tax control system concerning transfer pricing in foreign and Russian practice. The authors see the main principle of the system in the "armâ€™s length" concept which allows determination of the validity of the applied price for an intra-company transaction in comparison with its similar conditions and the market price. The authors of the paper suggest an integral system of tax control for transactions between interdependent entities, which includes: the legislatively regulated definition of the market price, the legislatively established regulation of transfer pricing tax control, and the mechanism of penalties for violation of the tax control law for transfer pricing. The latest innovations in the tax control system concerning transfer pricing are based on measures taken by OECD countries to combat the erosion of the tax base (the BEPS plan). The authors of the paper analyze certain provisions of this plan, such as documentation provided by holdings and transnational corporations for the purpose of tax control of transactions between interdependent entities; special attention is also paid to the analysis of tax control over transactions with intangible assets between interdependent entities under the BEPS (Base Erosion and Profit Shifting) plan. Based on the analysis of innovations in accordance with the Base Erosion and Profit Shifting plan, the authors of the article proposed a tax control system for transfer pricing taking into account the latest legislative changes.Â Â